Validation of the T-30 and swimming step test in adolescent competitive swimmers - Barber, J. W.; Williford, H. N.; Duey, W. J.; Pieri, S. R.; Barksdale, J. (Medicine & Science in Sports & Exercise, 1997)
Research design problems involved with the concepts employed in this study do not allow one to conclude that the swimming step test is a better predictor of appropriate training speeds than the T-30 swim.